CT perfusion-guided patient selection for endovascular recanalization in acute ischemic stroke: a multicenter study. (26th November 2012) - Turk, Aquilla S; Magarick, Jordan Asher; Frei, Don; Fargen, Kyle Michael; Chaudry, Imran; Holmstedt, Christine A; Nicholas, Joyce; Mocco, J; Turner, Raymond D; Huddle, Daniel; Loy, David; Bellon, Richard; et al.
Abstract : Background: The treatment of acute ischemic stroke is traditionally centered on time criteria, although recent evidence suggests that physiologic neuroimaging may be useful. In a multicenter study we evaluated the use of CT perfusion, regardless of time from symptom onset, in patients selected for intra-arterial treatment of ischemic stroke. Methods: Three medical centers retrospectively assessed stroke patients with a National Institute of Health Stroke Scale of ≥8, regardless of time from symptom onset. CT perfusion maps were qualitatively assessed. Patients with defined salvageable penumbra underwent intra-arterial revascularization of their occlusion. Functional outcome using the modified Rankin Score (mRS) was recorded. Results: Two hundred and forty-seven patients were selected to undergo intra-arterial treatment based on CT perfusion imaging. The median time from symptom onset to procedure was 6 h. Patients were divided into two groups for analysis: ≤8 h and >8 h from symptom onset to endovascular procedure. We found no difference in functional outcome between the two groups (42.8% and 41.9% achieved 90-day mRS ≤ 2, respectively (p=1.0), and 54.9% vs 55.4% (p=1.0) achieved 90-day mRS ≤ 3, respectively). Overall, 48 patients (19.4%) had hemorrhages, of which 20 (8.0%) were symptomatic, with no difference between the groups (p=1.0). Conclusions: In a multicenter study, we demonstrated similar rates of good functional outcome and intracranial hemorrhage in patients with ischemic stroke when endovascular treatment was performed based on CT perfusion selection rather than time-guided selection. Our findings suggest that physiologic imaging-guided patient selection rather than time for endovascular reperfusion in ischemic stroke may be effective and safe.